Effect of Implementation of Procurement of Goods/Services through E-Procurement and Internal Control on Fraud Prevention in Sidoarjo Regency - Putri Laras; Imelda Dian Rahmawati (Indonesian Journal of Public Policy Review, 2022)
The purpose of this research is to find out whether e-procurement and internal control variables can affect fraud prevention. This type of research used quantitative research. The sample used was 36 employees of the Procurement of Goods/Services using probability sampling and random sampling methods. Data obtained by distributing questionnaires to employees of the procurement of goods/services to be answered. The analytical tool used to help process the data is SPSS software version 18.0. The analysis technique uses multiple linear. Of the 36 questionnaires distributed, only 35 were returned and could be processed. The results of the partial test. Variable X1 namely e-procurement showed no effect on fraud prevention of 0.265 and variable X2, namely internal control, showed an effect on fraud of 7.380. Simultaneously, the variables X1 and X2 have an effect on fraud of 28,716.